The Mediating Effects of Specific Types of Self-Efficacy on the Relationship between Math Anxiety and Performance - Molly M. Jameson; Celeste Dierenfeld; Julia Ybarra (MDPI AG, 2022)
The negative relationship between math anxiety and math performance is well-supported in the literature. The important role of students' math self-efficacy (i.e., their confidence in their ability to successfully complete specific math tasks) in this relationship is also established. Self-efficacy is extremely specific, however, and it is possible that additional types of self-efficacy can play a role in the relationship between anxiety and performance. This study surveyed 118 undergraduate students on their math anxiety, math performance, math self-efficacy, emotional self-efficacy, and emotional self-efficacy specifically in math to determine the mediating effects of these specific types of self-efficacy. Hierarchical linear regression shows that math self-efficacy continues to fully mediate the relationship between anxiety and performance; in the current study, emotional self-efficacy partially mediated the relationship while emotional self-efficacy specifically in math did not. The role of emotional self-efficacy should be further explored, as these findings are contrary to previous work. Educational interventions should continue to emphasize building students' math confidence to improve the math performance of math-anxious students.